Association of occupational dust exposure with combined chronic obstructive pulmonary disease and pneumoconiosis: a cross-sectional study in China - Yali Fan; Qiao Ye; Wenjing Xu; Yuanying Wang; Yiran Wang; Shiwen Yu (BMJ Open)
Objectives Occupational dust exposure may induce various lung diseases, including pneumoconiosis and chronic obstructive pulmonary disease (COPD). The features of combined COPD and pneumoconiosis have not been well described, and this may hamper the management. This study aimed to describe the prevalence and characteristics as well as the risk factors of the combined diseases.Design A cross-sectional study.Setting and participants 758 patients with pneumoconiosis were recruited at a single-medical centre. Of these, 675 patients with pneumoconiosis, including asbestosis, silicosis, coal workers’ pneumoconiosis and other pneumoconiosis, was eligible for analysis.Primary outcome measures COPD was diagnosed based on clinical features and/or history of exposure to risk factors and post bronchodilator forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) ratio <0.7. Clinical data were collected from predesigned medical reports. The patients underwent both chest radiograph and high-resolution CT scans. Risk factors for combined COPD and pneumoconiosis were analysed using regression analysis.Results COPD prevalence overall was 32.7% (221/675) and was the highest in silicosis (84/221) and coal workers’ pneumoconiosis (100/221). COPD prevalence increased with smoking pack-years, dust exposure duration and pneumoconiosis stage. Patients with combined diseases had lower body mass index, higher smoking index and worse pulmonary function. Risk factors for combined diseases included heavy smoking, silica or coal exposure and advanced pneumoconiosis. The interaction between dust exposure and smoking in COPD was also identified. The risk of combined COPD significantly increased with heavy smoking and silica or coal exposure (OR 5.49, 95% CI 3.04 to 9.93, p<0.001).Conclusions COPD is highly prevalent in patients with pneumoconiosis, especially patients with silicosis and coal workers’ pneumoconiosis. Occupational dust exposure as well as heavy smoking is associated with an increased risk of combined COPD and pneumoconiosis, which demands an effective preventive intervention.